2002
DOI: 10.1152/ajplung.00478.2001
|View full text |Cite
|
Sign up to set email alerts
|

In vivo and in vitro uptake of surfactant lipids by alveolar type II cells and macrophages

Abstract: / ajplung.00478.2001.-The uptake of fluorescent-labeled liposomes (with a surfactant-like composition) by alveolar macrophages and alveolar type II cells was studied using flow cytometry, in vivo by instillation of the labeled liposomes in the trachea of ventilated rats followed by isolation of the alveolar cells and determination of the cell-associated fluorescence, and in vitro by incubation of isolated alveolar cells with the fluorescent liposomes. The results show that the uptake of liposomes by the alveol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
31
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(38 citation statements)
references
References 19 publications
7
31
0
Order By: Relevance
“…Using a nondegradable analog of dipalmitoylphosphatidylcholine or flow cytometry, others found that although macrophages take up liposomes in vivo, type II cells make a greater contribution to the uptake and metabolism of lipids (35,37). In this study, we found radioactivity associated with macrophages and type II cells after instillation of 125 I-SP-A and perfusion of the lung for 1 h followed by isolation of the cells.…”
Section: )supporting
confidence: 52%
“…Using a nondegradable analog of dipalmitoylphosphatidylcholine or flow cytometry, others found that although macrophages take up liposomes in vivo, type II cells make a greater contribution to the uptake and metabolism of lipids (35,37). In this study, we found radioactivity associated with macrophages and type II cells after instillation of 125 I-SP-A and perfusion of the lung for 1 h followed by isolation of the cells.…”
Section: )supporting
confidence: 52%
“…However, although the effects of PC16:0/14:0 were concentration dependent and mostly required an uptake during 48 h preincubation, the amount of PC16:0/14:0 taken up into macrophages from Curosurf approximated that of the isolated compound given as liposomes. The principle difference in uptake between Curosurf and PC species might be due to lipophilic SP-B and SP-C, anionic PGs, and neutral lipids being present in animalderived surfactants (17). However, our data demonstrate that internalization of either compound is an active process, because it was blunted at 4jC (Fig.…”
Section: Discussionmentioning
confidence: 59%
“…The organic phase was mixed with Curosurf or PC species in a molar ratio of 5:95 (17) and dried under a stream of nitrogen. Lissamine-DHPE-labeled liposomes were analyzed by FACS.…”
Section: Preparation Of Lissamine-dhpe-labeled Liposomes and Assessmementioning
confidence: 99%
“…Liposomes were prepared as described previously (24). Details are provided in the online supplement.…”
Section: Liposome Preparationmentioning
confidence: 99%